Answer:
![-13x-23](https://img.qammunity.org/2023/formulas/mathematics/high-school/1hdnojbdccfb2gurtl4f2033f3z8eyrn75.png)
Explanation:
Given sequence:
![x-9, -x-11, -3x-13](https://img.qammunity.org/2023/formulas/mathematics/high-school/zq6hbaebgqc64tioi934tlwfyoz1r07d3l.png)
Therefore,
General form of an arithmetic sequence:
![a_n=a+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/t99kk5roieipg56xa37yseewl9ybc4zh6i.png)
(where a is the first term and d is the common difference)
To find the common difference, subtract a term from the next term:
![\begin{aligned}d & =a_2-a_1\\ & =(-x-11)-(x-9)\\ & = -x-11-x+9\\ & = -2x-2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/l6qbqgvhi1wsq93jhxtnxcavix2cgkpb23.png)
Therefore,
![a_n & =(x-9)+(n-1)(-2x-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/3trhtdpb8hyrwi3q1gqxflugztdt2fd4lq.png)
To find the 6th term, input n = 6 into the equation:
![\begin{aligned}\implies a_6 & =(x-9)+(6-1)(-2x-2)\\ & = (x-9)+7(-2x-2)\\ & = x-9-14x-14\\ & = -13x-23\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6okagvj15injgyhbycccpwuqfted920a2h.png)